DARI LIMBAH MENJADI KEKUATAN: REKAYASA MATERIAL KONSTRUKSI BERKELANJUTAN, MENGIDENTIFIKASI STRATEGI PENGEMBANGAN MATERIAL MAJU BERBASIS SAMPAH PLASTIK: PENDEKATAN SWOT-AHP TERINTEGRASI - Moniaga, Fenny; Kafrain, I Gede Yohan; Pandey, Raymond David; Korobu, Eirene (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2026)
This research aims to identify strategies for developing construction materials based on plastic waste to address environmental issues and support sustainable construction. The urgency of this research is based on the increasing volume of waste at the Sumompo landfill in Manado City, which reaches around 330 tonnes per day, as well as challenges in implementing construction materials made from plastic waste. Waste management in Manado faces complex and interrelated problems. Previous research has shown the technical potential of waste polymer bricks and concrete, but it is still constrained by industrial readiness, regulations, and public acceptance. The integration of these issues points to the urgency of research into the development of applicable plastic waste-based construction materials. Therefore, this study focuses on the utilisation of plastic waste as a construction material to reduce environmental impact and improve the sustainability of the construction sector. The analysis approach in the existing waste management system at the Sumompo landfill site, Evaluation of Plastic Waste Management and Utilisation using a SWOT-AHP-based strategy approach. SWOT analysis is used to identify internal factors (strengths and weaknesses) and external factors (opportunities and threats). Subsequently, AHP is used to prioritise implementation strategies, with the findings of the analysis showing that a multi-sector approach is needed to optimise the use of plastic waste as a construction material, taking into account industry readiness, regulations, and public acceptance as key factors for successful implementation. These findings provide strategic recommendations for the development of environmentally friendly construction materials. The results of the weighting of the strategic goals of technological feasibility, environmental impact, and policy and regulatory framework development are still high.Keywords: Sustainable Construction Materials, Plastic Waste, SWOT-AHP Analysis